Conductive paste for flexible fabric and preparation method thereof

By using high-performance materials such as carbon nano hollow fibers and MXene in the conductive paste for flexible fabrics, and combining crosslinking agents and other components, the problem of poor quality of flexible fabrics is solved, and the conductive properties are significantly improved and the weather resistance and bending resistance are enhanced.

CN119694629AInactive Publication Date: 2025-03-25XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510206803.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The quality of the existing conductive paste for flexible fabrics is poor, resulting in increased resistance during bending and use, and insufficient weather resistance and bending resistance.

Method used

Using conductive agents including carbon nano hollow fibers and MXene, combined with crosslinking agents, dispersants, viscosity reducing agents and solvents, a conductive paste with excellent weather resistance and bending resistance is formed through specific ratios and preparation methods.

Benefits of technology

The weather resistance and bending resistance of the conductive paste are significantly improved, the resistance change rate is reduced, the interaction between the conductive material and other materials is enhanced, and the conductivity of the flexible fabric is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694629A_ABST
    Figure CN119694629A_ABST
Patent Text Reader

Abstract

The invention provides conductive paste for a flexible fabric and a preparation method of the conductive paste, and relates to the technical field of conductive materials. The conductive paste for the flexible fabric comprises a conductive agent, a cross-linking agent, a dispersing agent, a viscosity reducer and a solvent, wherein the weight ratio of the conductive agent to the cross-linking agent to the dispersing agent to the viscosity reducer to the solvent in the conductive paste is (1-20): (0.1-1): (0.5-3): (0.01-0.05): (70-90); the conductive agent comprises carbon nano hollow fibers and MXene, and the weight ratio of the carbon nano hollow fibers to the conductive agent is 10%-75%. The quality of the conductive paste for the flexible fabric can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of conductive materials, and in particular to a conductive paste for flexible fabrics and a preparation method thereof. Background Art

[0002] With the rapid economic growth and the improvement of the quality of life, people's demand for wearable smart electronic devices such as smart watches, smart clothing, smart glasses, etc. is growing. Wearable smart electronic devices have unique bending, curvature and ductility, which makes them show broad application prospects in many fields such as electronics, information, national defense, and medical treatment.

[0003] Conductive paste is widely used in the field of flexible electronic wearables because of its excellent conductivity and strong adhesion. It is mainly composed of conductive materials, glass powder and organic carriers. However, there is a common problem that the quality of conductive paste for flexible fabrics is poor.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present disclosure is to provide a conductive paste for flexible fabrics and a preparation method thereof, thereby overcoming the problem of poor quality of the conductive paste for flexible fabrics at least to a certain extent.

[0006] According to a first aspect of the present disclosure, a conductive paste for flexible fabrics is provided, comprising a conductive agent, a cross-linking agent, a dispersant, a viscosity reducer and a solvent, wherein the weight ratio of the conductive agent, the cross-linking agent, the dispersant, the viscosity reducer and the solvent in the conductive paste is (1-20): (0.1-1): (0.5-3): (0.01-0.05): (70-90); the conductive agent comprises carbon nano hollow fibers and MXene, and the weight ratio of the carbon nano hollow fibers to the conductive agent is 10% to 75%.

[0007] Optionally, the weight ratio of MXene to the conductive agent is 25% to 90%.

[0008] Optionally, the MXene has a thickness of 1 nm to 10 nm and a specific surface area of ​​50 m 2 / g to 90m 2 / g; the diameter of the carbon nano hollow fiber is 2nm to 30nm, the length is 2μm to 100μm, and the specific surface area is 500m 2 / g to 2500m 2 / g.

[0009] Optionally, the MXene is one or more of hydroxylated MXene, aminated MXene and carboxylated MXene; the carbon nano hollow fibers are one or more of hydroxylated carbon nano hollow fibers, aminated carbon nano hollow fibers and carboxylated carbon nano hollow fibers.

[0010] Optionally, the cross-linking agent is any one of 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, and 1H, 1H, 2H, 2H-perfluorodecyltriethylsilane.

[0011] Optionally, the dispersant is one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, polyvinylidene fluoride, sodium carboxymethyl cellulose, polytetrafluoroethylene, and polyester polyoxyethylene ether.

[0012] Optionally, the viscosity reducing agent is one or more of anhydrous piperazine, potassium hydroxide, and sodium hydroxide.

[0013] Optionally, the solvent is any one of N-methylpyrrolidone, deionized water, and N-dimethylformamide.

[0014] According to the second aspect of the present disclosure, a method for preparing a conductive paste for flexible fabrics is provided, and the conductive paste for flexible fabrics is any one of the conductive pastes for flexible fabrics described above. The preparation method comprises: dissolving a dispersant and a viscosity reducer in a solvent to obtain a first mixture; adding MXene to the first mixture to obtain a second mixture after dispersion; adding carbon nano hollow fibers to the second mixture to obtain a third mixture after dispersion; adding a crosslinking agent to the third mixture to obtain a fourth mixture after dispersion; adding the fourth mixture to a three-roll grinder and grinding for 3 to 5 times to obtain a conductive paste for flexible fabrics.

[0015] Optionally, dissolving the dispersant and the viscosity reducer in the solvent to obtain a first mixture comprises: dissolving the dispersant and the viscosity reducer in the solvent at a dissolution temperature of 25° C. to 35° C. for a dissolution time of 1 hour to 6 hours to obtain the first mixture.

[0016] In the scheme of the exemplary embodiment of the present disclosure, carbon nano hollow fibers and MXene with excellent mechanical properties are selected to generate the conductive agent, which can enhance the stability of the conductive path and maintain the bending resistance of the conductive paste. In addition, based on the effect of the cross-linking agent, the interaction between the conductive material and other materials is enhanced, and the prepared paste has excellent weather resistance and bending resistance, and the quality of the conductive paste is improved.

[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0019] Figure 1 A flow chart schematically shows a method for preparing a conductive paste for flexible fabric according to an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION

[0020] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0021] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same figure numbers in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", "third", "fourth", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.

[0022] For the conductive paste for flexible fabrics, the bonding between its components and at the interface with the flexible substrate is weak. This weak interaction will have two effects: first, over time, the conductive material will migrate inside the paste, causing the resistance to change; second, when the flexible substrate is bent, creases and shedding will occur, which leads to increased resistance.

[0023] In order to improve the quality of the conductive paste, the embodiment of the present disclosure provides a new conductive paste for flexible fabrics, which includes a conductive agent, a cross-linking agent, a dispersant, a viscosity reducer and a solvent. The weight ratio of the conductive agent, the cross-linking agent, the dispersant, the viscosity reducer and the solvent in the conductive paste is (1~20): (0.1~1): (0.5~3): (0.01~0.05): (70~90); the conductive agent includes carbon nano hollow fibers and MXene, and the weight ratio of the carbon nano hollow fibers to the conductive agent is 10% to 75%. Among them, the carbon nano hollow fibers can also be called hollow carbon nanofibers. MXene is a two-dimensional material, which can usually be composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers.

[0024] According to some embodiments of the present disclosure, the conductive agent is composed of carbon nano hollow fibers and MXene. In this case, the weight ratio of MXene to the conductive agent is 25% to 90%.

[0025] In addition, in addition to carbon nano hollow fibers and MXene, the conductive agent may also include graphite, metal-based conductive agents, etc., which is not limited in the present disclosure.

[0026] The thickness of the MXene used is 1nm to 10nm, and the specific surface area is 50m 2 / g to 90m 2 / g. The carbon nano hollow fibers used have a diameter of 2nm to 30nm, a length of 2μm to 100μm, and a specific surface area of ​​500m 2 / g to 2500m 2 / g.

[0027] Specifically, the MXene is one or more of hydroxylated MXene, aminated MXene and carboxylated MXene; the carbon nano hollow fiber is one or more of hydroxylated carbon nano hollow fiber, aminated carbon nano hollow fiber and carboxylated carbon nano hollow fiber.

[0028] According to some embodiments of the present disclosure, the crosslinking agent may include a fluorinated silane. Specifically, the crosslinking agent may be any one of 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, and 1H, 1H, 2H, 2H-perfluorodecyltriethylsilane.

[0029] The dispersant may be one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, polyvinylidene fluoride, sodium carboxymethyl cellulose, polytetrafluoroethylene, and polyester polyoxyethylene ether.

[0030] The viscosity reducing agent may be one or more of anhydrous piperazine, potassium hydroxide, and sodium hydroxide.

[0031] The solvent may be any one of N-methylpyrrolidone, deionized water, and N-dimethylformamide.

[0032] The disclosed embodiments utilize carbon nano hollow fibers and MXene with excellent mechanical properties to enhance the stability of the conductive path and maintain the bending resistance of the conductive paste. The weather resistance of the paste can be enhanced by selecting fluorinated silanes with high chemical stability and low surface energy. At the same time, the silanol groups of fluorosilanes react with the hydroxyl groups of conductive materials with different functional groups and flexible substrates to enhance the interaction between the paste and the substrate, improve the bending resistance, facilitate the use in the flexible fabric printing process, and facilitate the performance of the flexible smart fabric in the later stage.

[0033] Reference below Figure 1 The preparation method of the conductive paste for flexible fabric according to the embodiment of the present disclosure is described. The conductive paste for flexible fabric mentioned here is any one of the conductive pastes for flexible fabric in the above embodiments. Figure 1 The method for preparing the conductive paste for flexible fabric according to the embodiment of the present disclosure may include the following steps: S10. Dissolving the dispersant and the viscosity reducer in the solvent to obtain a first mixture.

[0034] Specifically, the dissolution temperature is 25° C. to 35° C., and the dissolution time is 1 h to 6 h.

[0035] S12. Add MXene to the first mixture, and obtain a second mixture after dispersion.

[0036] Specifically, a homogenizer may be used for dispersion for 10 to 30 minutes.

[0037] S14. Adding the carbon nano hollow fibers to the second mixture to obtain a third mixture after dispersion.

[0038] Specifically, a homogenizer may be used for dispersion for 20 to 40 minutes.

[0039] S16. Adding the crosslinking agent to the third mixture, and obtaining a fourth mixture after dispersion.

[0040] Specifically, a homogenizer may be used for dispersion for 10 to 30 minutes.

[0041] S18. Add the fourth mixture into a three-roll mill and grind it 3 to 5 times to obtain a conductive paste for flexible fabrics.

[0042] The embodiments of the present disclosure are described below by way of examples.

[0043] Example 1 Three groups of experiments were designed to compare MXene slurry, MXene / carbon nano hollow fiber slurry, and fluorosilane-reinforced MXene / carbon nano hollow fiber slurry.

[0044] Test 1: Dissolve 0.2g of sodium dodecyl sulfate and 0.03g of sodium hydroxide in 80g of N-methylpyrrolidone at a dissolution temperature of 25°C to 35°C for 1h to 6h to obtain a mixed solution; add 20g of MXene to the mixed solution and disperse it for 10min to 30min using a homogenizer to obtain a MXene slurry; disperse it for 10min to 30min using a homogenizer; then add it to a three-roll mill and grind it 3 to 5 times to obtain the final MXene slurry. Subsequently, the conductive slurry was coated on the surface of the polyester fabric by screen printing for testing.

[0045] Test 2: Dissolve 0.2g of sodium dodecyl sulfate and 0.03g of sodium hydroxide in 80g of N-methylpyrrolidone at a dissolution temperature of 25°C to 35°C and a dissolution time of 1h to 6h to obtain a mixed solution; add 20g of MXene to the mixed solution and disperse it for 10min to 30min using a homogenizer to obtain a MXene slurry; add 10g of carbon nano hollow fiber to the MXene slurry and disperse it for 20min to 40min using a homogenizer to obtain a MXene / carbon nano hollow fiber slurry; then add it to a three-roll grinder and grind it 3 to 5 times to obtain a MXene / carbon nano hollow fiber slurry. Subsequently, the conductive slurry was coated on the surface of the polyester fabric by screen printing for testing.

[0046] Test 3: Dissolve 0.2g of sodium dodecyl sulfate and 0.03g of sodium hydroxide in 80g of N-methylpyrrolidone at a dissolution temperature of 25°C to 35°C and a dissolution time of 1h to 6h to obtain a mixed solution; add 20g of MXene to the mixed solution and disperse it for 10min to 30min using a homogenizer to obtain a MXene slurry; add 10g of carbon nano hollow fiber to the MXene slurry and disperse it for 20min to 40min using a homogenizer to obtain a carbon nano hollow fiber / MXene slurry; add 0.02g of 1H, 1H, 2H, 2H-perfluorooctyl trimethoxysilane to the carbon nano hollow fiber / MXene slurry and disperse it for 10min to 30min using a homogenizer; then add it to a three-roll grinder and grind it 3 to 5 times to obtain a carbon nano hollow fiber composite conductive slurry. The conductive slurry was subsequently coated on the surface of the polyester fabric by screen printing for testing.

[0047] The difference between the above-mentioned test 1 and test 2 is that the carbon nano hollow fiber is added in the test 2, and the difference between the test 2 and the test 3 is that 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane is added in the test 3. The test results are shown in Table 1: Table 1

[0048] By comparing the results of experiments 1, 2 and 3, it can be found that with the addition of carbon nano hollow fibers and 1H, 1H, 2H, 2H-perfluorooctyl trimethoxysilane, the resistance change rate after 7 days and 200 bends shows a decreasing trend. This shows that carbon nano hollow fibers and 1H, 1H, 2H, 2H-perfluorooctyl trimethoxysilane can enhance the weather resistance and bending resistance of the conductive paste.

[0049] Example 2 Four groups of experiments were designed to compare the effects of different amounts of carbon nano hollow fiber slurry addition.

[0050] The difference between Experiment 4 and Experiment 3 is that the amount of carbon nano hollow fibers added in Experiment 4 is 4 g.

[0051] The difference between Experiment 5 and Experiment 3 is that the amount of carbon nano hollow fibers added in Experiment 5 is 6 g.

[0052] The difference between Experiment 6 and Experiment 3 is that the amount of carbon nano hollow fibers added in Experiment 6 is 8 g.

[0053] The difference between Experiment 7 and Experiment 3 is that the amount of carbon nano hollow fibers added in Experiment 7 is 12 g.

[0054] The test results are shown in Table 2: Table 2

[0055] By comparing the results of tests 3, 4, 5, 6 and 7, it can be found that with the increase in the amount of carbon nano hollow fibers added, the resistance change rate after 7 days and 200 bends shows a trend of first decreasing and then increasing.

[0056] Example 3 Four groups of experiments were designed to compare the effects of different fluorosilane addition amounts.

[0057] The difference between Experiment 8 and Experiment 3 is that the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane added in Experiment 8 is 0.01 g.

[0058] The difference between Experiment 9 and Experiment 3 is that the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane added in Experiment 9 is 0.03 g.

[0059] The difference between Experiment 10 and Experiment 3 is that the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane added in Experiment 10 is 0.04 g.

[0060] The difference between Experiment 11 and Experiment 3 is that the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane added in Experiment 11 is 0.05 g.

[0061] The test results are shown in Table 3: Table 3

[0062] By comparing the results of tests 3, 8, 9, 10 and 11, it can be found that with the increase in the amount of 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane added, the resistance change rate after 7 days and 200 bending times shows a trend of first decreasing and then increasing.

[0063] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.

[0064] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0065] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.

[0066] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A conductive paste for flexible fabrics, characterized in that: The conductive paste comprises a conductive agent, a cross-linking agent, a dispersant, a viscosity reducer and a solvent, wherein the weight ratio of the conductive agent, the cross-linking agent, the dispersant, the viscosity reducer and the solvent in the conductive paste is (1-20): (0.1-1): (0.5-3): (0.01-0.05): (70-90); The conductive agent includes carbon nano hollow fibers and MXene, and the weight ratio of the carbon nano hollow fibers to the conductive agent is 10% to 75%.

2. The conductive paste for flexible fabric according to claim 1, characterized in that: The weight ratio of the MXene to the conductive agent is 25% to 90%.

3. The conductive paste for flexible fabric according to claim 1 or 2, characterized in that: The thickness of the MXene is 1 nm to 10 nm, and the specific surface area is 50 m 2 / g to 90m 2 / g; The carbon nano hollow fiber has a diameter of 2nm to 30nm, a length of 2μm to 100μm, and a specific surface area of ​​500m 2 / g to 2500m 2 / g.

4. The conductive paste for flexible fabric according to claim 1 or 2, characterized in that: The MXene is one or more of hydroxylated MXene, aminated MXene and carboxylated MXene; The carbon nano hollow fibers are one or more of hydroxylated carbon nano hollow fibers, amination carbon nano hollow fibers and carboxylation carbon nano hollow fibers.

5. The conductive paste for flexible fabric according to claim 1, characterized in that: The cross-linking agent is any one of 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethylsilane.

6. The conductive paste for flexible fabric according to claim 1, characterized in that: The dispersant is one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, polyvinylidene fluoride, sodium carboxymethyl cellulose, polytetrafluoroethylene, and polyester polyoxyethylene ether.

7. The conductive paste for flexible fabric according to claim 1, characterized in that: The viscosity reducing agent is one or more of anhydrous piperazine, potassium hydroxide and sodium hydroxide.

8. The conductive paste for flexible fabric according to claim 1, characterized in that: The solvent is any one of N-methylpyrrolidone, deionized water and N-dimethylformamide.

9. A method for preparing a conductive paste for flexible fabrics, characterized in that: The conductive paste for flexible fabric is the conductive paste for flexible fabric according to any one of claims 1 to 8; wherein the preparation method comprises: dissolving a dispersant and a viscosity reducing agent in a solvent to obtain a first mixture; Adding MXene to the first mixture to obtain a second mixture after dispersion; adding the carbon nano hollow fibers into the second mixture to obtain a third mixture after dispersion; adding a crosslinking agent to the third mixture to obtain a fourth mixture after dispersion; The fourth mixture was added into a three-roll mill and ground for 3 to 5 times to obtain a conductive paste for flexible fabrics.

10. The preparation method according to claim 9, characterized in that: Dissolving a dispersant and a viscosity reducing agent in a solvent to obtain a first mixture, comprising: The dispersant and the viscosity reducer are dissolved in the solvent at a dissolution temperature of 25° C. to 35° C. for a dissolution time of 1 h to 6 h to obtain a first mixture.

Citation Information

Patent Citations

  • Graphene modified material as well as preparation method and application thereof

    CN107747210A

  • High-conductivity and high-stability carbon nanotube compound conductive paste for lithium ion battery and preparation method of high-conductivity and high-stability carbon nanotube compound conductive paste

    CN113035407A

  • Conductive paste, preparation method and electronic device comprising conductive paste

    CN115458205A

  • Polypropylene composition for high-weather-resistance and high-flame-retardance injection molding material and polypropylene injection molding material

    CN115477811A

  • Metallic ink, method for producing metallic ink, substrate for display device and method for producing substrate for display device

    CN1869134A